The Impact of Biostarter Em-4 and Cow Feces on the Quality of Biogas from Sugarcane Bagasse Fibre - Fani, Meylin Sir; Darvina, Yenni; Hidayat, Rahmat (PILLAR OF PHYSICS, 2024)
Energy demand is increasing every year. The abundant and unlimited use of energy causes the supply of energy availability to be depleted. Non-renewable energy if used excessively will cause an energy crisis. This is a serious problem that must be overcome by finding alternative or renewable energy. Renewable energy can be created from biomass. Biomass from agricultural waste in the form of bagasse fibre (BF) and livestock waste in the form of cow feces (CF) can be used as biogas filling material. The problem raised in this research is the role of EM-4 biostarter and cow feces from bagasse fibre on the pH, temperature and pressure of biogas. The composition variations of AT and cow feces in this study were 50% BF : 50% CF, 40% BF : 60% CF and 30% BF : 70% CF  without using EM-4 biostarter and using EM-4 biostarter. Batch type digester reactor type. The method used was experimental method. The results show that EM-4 biostarter and cow feces affect the quality of biogas when viewed from indicators such as pH, gas pressure and gas temperature. Biostarter EM-4 accelerates the fermentation process so that more gas is produced and the gas pressure is higher. The more cow feces used, the more gas is produced. indicators of good biogas quality are indicated by blue flames. The greater the gas pressure produced, the greater the energy contained in the biogas.